2022
DOI: 10.1101/2022.06.10.495644
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strand-resolved mutagenicity of DNA damage and repair

Abstract: SummaryDNA base damage is a major source of oncogenic mutations1. Such damage can produce strand-phased mutation patterns and multiallelic variation through the process of lesion segregation2. Here, we exploited these properties to reveal how strand-asymmetric processes, such as replication and transcription, shape DNA damage and repair. Despite distinct mechanisms of leading and lagging strand replication3,4, we observe identical fidelity and damage tolerance for both strands. For small DNA adducts, our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 86 publications
2
12
0
Order By: Relevance
“…Interestingly we observed that the little evolution we observe in NER deficient strains is not diminished in the presence of thiourea, supporting our model that NER-dependent mutagenesis is mostly due to lesions caused by oxidative stress. This is consistent with the mutagenic footprint of NER observed in mammalian cells 31 . Therefore, in addition to showing that NER is universally mutagenic and transcription-associated in bacteria, our findings likely explain the main source of NER-dependent mutagenesis not only in bacteria, but also in higher eukaryotes.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Interestingly we observed that the little evolution we observe in NER deficient strains is not diminished in the presence of thiourea, supporting our model that NER-dependent mutagenesis is mostly due to lesions caused by oxidative stress. This is consistent with the mutagenic footprint of NER observed in mammalian cells 31 . Therefore, in addition to showing that NER is universally mutagenic and transcription-associated in bacteria, our findings likely explain the main source of NER-dependent mutagenesis not only in bacteria, but also in higher eukaryotes.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, a recent pre-print has proposed that DNA lesions that are in close proximity and on different strands lead to mutagenic NER, using a mouse liver cancer model in which cells are exposed to high levels of the DNA damaging agent diethylnitrosamine 31 . Moreover, NER has been found to be pro-mutagenic in stationary phase yeast cells irradiated with UV light [32][33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSH2 functions as a dimer with MSH6, which is likely targeted to H3K4me1 via its Tudor domain [10,44]. Additional recent studies that support the core findings of [1] include reports of (i) reduced germline and somatic mutations rates in transcribed genes, in genome regions marked by epigenomic features characteristic for gene activation, and in gene bodies, observed in several algae, plants as well as humans and nematodes [17,21,36,42,[47][48][49][50][51][52]; (ii) relationships between histone modifications -especially those linked to gene activation -, mutation rates and DNA repair across diverse species [51,[53][54][55][56][57][58][59][60]; and 8 (iii) H3K4me1 affecting rates of CRISPR-mediated mutagenesis in plants [61]. That the role of histone modifications in driving DNA repair localization is well-established is also reflected in cancer therapeutics targeting histone states being widely pursued (e.g., [62][63][64][65][66]).…”
Section: Discussionmentioning
confidence: 91%
“…The third possibility would involve a previously uncharacterized mechanism associated with transcription specific to Pol III that is highly different from Pol II in protein composition 39 . Interestingly, it was recently shown that damage-induced mutations can accumulate on the non-transcribed strand outside of replication 4,40 . However, this mechanism creates a very strong mutational asymmetry that we were not able detect for Pol III transcripts, implying other mechanisms.…”
mentioning
confidence: 99%